A molecular precursor route to quaternary chalcogenide CFTS (Cu2FeSnS4) powders as potential solar absorber materials. Issue 42 (5th August 2019) - Alanazi, Abdulaziz M.; Alam, Firoz; Salhi, Abdelmajid; Missous, Mohamed; Thomas, Andrew G.; O'Brien, Paul; Lewis, David J.
Abstract : In the present work we report on the synthesis of a tetragonal phase of stannite Cu2 FeSnS4 powder from Sn(ii ) and Sn(iv ) using a solvent free melt method using a mixture of Cu, Fe, Sn(ii )/Sn(iv ) O -ethylxanthates. Abstract : In the present work we report on the synthesis of tetragonal stannite Cu2 FeSnS4 powders using a solvent free melt method using a mixture of Cu, Fe, and Sn(ii )/Sn(iv ) O -ethylxanthates heated at different temperatures. The as-synthesized powders were characterized by powder X-ray diffraction (p-XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), UV-Vis absorption spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy, which confirm the successful synthesis of stannite CFTS. Optical measurements show that Cu2 FeSnS4 powders have visible light absorption onsets in the far red with direct band gap energies in the range 1.32–1.39 eV which are suitable for acting as efficient absorber layers in solar cells. Electronic characterisation of these materials deposited as thin films by spin coating show that they are p type semiconductors with respectable carrier mobilities of ca. 60 cm 2 V −1 s −1 with carrier densities on the order of 10 14 cm −1 .